Effect of pressure and temperature on supercritical fluid extraction of patchouli (Pogostemon cablin) essential oil - Tan, Teng Ju; Muhammad Shahrin, Artikah (2015)
Patchouli (Pogostemon cablin) essential oil has been widely used in cosmetic and perfume industries, in alternative medicines, as well as in food industry as natural food additives. This study aims to determine the effect of temperature and pressure of supercritical fluid extraction (SFE) by carbon dioxide on the yield and quality of patchouli essential oil. The total oil content (TOC) analysis showed that the highest yield was obtained under the pressure of 60 MPa at 55°C, with 3.0586 ± 0.23 % TOC and the lowest yield was observed under the pressure of 10 MPa at 55°C, with only 0.5648 ± 0.19 % TOC. The gas chromatography-mass spectrometry (GC-MS) analysis demonstrated that SFE at 10 MPa; 35°C gave the highest composition of patchoulol (73.65 ± 3.60 %), while SFE at 60 MPa; 55°C resulted in highest amount of α-patchoulene (5.01 ± 0.20 %). Commercial patchouli essential oil produced by steam distillation was found to acquire the least amount of patchoulol among all (38.95 %), but contained fairly high concentration of α-patchoulene (3.86 %). The optimum conditions for SFE of patchouli essential oil were 60 MPa; 55°C, which gave the highest oil yield with 59.30 ± 6.16 % of total percentage of both patchoulol and α-patchoulene. The study elucidated that the oils extracted by SFE had higher quality compared to the steam-distilled oil, based on the quantity of two important compounds (patchoulol and α-patchoulene) that specifically determined the quality of the patchouli oil.